Long lasting perfume – A review of synthetic musks in WWTPs. (1st February 2015) - Homem, Vera; Silva, José Avelino; Ratola, Nuno; Santos, Lúcia; Alves, Arminda
Abstract: Synthetic musks have been used for a long time in personal care and household products. In recent years, this continuous input has increased considerably, to the point that they were recognized as emerging pollutants by the scientific community, due to their persistence in the environment, and hazardous potential to ecosystems even at low concentrations. The number of studies in literature describing their worldwide presence in several environmental matrices is growing, and many of them indicate that the techniques employed for their safe removal tend to be ineffective. This is the case of conventional activated sludge treatment plants (WWTPs), where considerable loads of synthetic musks enter mainly through domestic sewage. This review paper compiles and discusses the occurrence of these compounds in the sewage, effluents and sludge, main concentration levels and phase distributions, as well as the efficiency of the different methodologies of removal applied in these treatment facilities. To the present day, it has been demonstrated that WWTPs lack the ability to remove musks completely. This shows a clear need to develop new effective and cost-efficient remediation approaches and foresees potential for further improvements in this field. Highlights: WWTPs are one of the main potential sources of environmental contamination for musks. Musks tend to be removed from wastewaters by sorption on sludge. HHCB and AHTN are predominant musks regarding detection frequencies and levels. WWTPs remove an important fraction of the musks load, but mainly from the liquid to the solid phase.